eCM 2015
DOI: 10.22203/ecm.v030a12
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineering scaled-up, anatomically shaped osteochondral constructs for joint resurfacing

Abstract: Arthroplasty is currently the only surgical procedure available to restore joint function following articular cartilage and bone degeneration associated with diseases such as osteoarthritis (OA). A potential alternative to this procedure would be to tissue-engineer a biological implant and use it to replace the entire diseased joint. The objective of this study was therefore to tissue-engineer a scaled-up, anatomically shaped, osteochondral construct suitable for partial or total resurfacing of a diseased join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…Statistical analysis was performed as previously described [47] . Briefly tukey's test for multiple comparisons was used to compare conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis was performed as previously described [47] . Briefly tukey's test for multiple comparisons was used to compare conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A 3D molding technique was developed to fabricate tissue-engineered large-scale osteochondral constructs (typical size over 2 cm) of alginate hydrogel with anatomical shapes [280]. The fabrication process involved 3D medical imaging of femoral condyle and tibial plateau, modeling, two-part reverse mold design/fabrication, and MSC/chondrocyte-laden alginate/agarose hydrogel construct molding.…”
Section: Advanced Manufacturing Techniques For Engineering Osteochmentioning
confidence: 99%
“…BMSCs are an attractive option, but their propensity for osteogenesis limits their use for meniscal tissue engineering (Makris, Hadidi, & Athanasiou, 2011;Van der Bracht, Verdonk, Verbruggen, Elewaut, & Verdonk, 2007). We have demonstrated that infrapatellar fat pad-derived stem cells (FPSCs) represent an attractive alternative to BMSCs for engineering of cartilaginous tissues (Buckley et al, 2010;Carroll, Buckley, & Kelly, 2014;Luo, O'Reilly, Thorpe, Buckley, & Kelly, 2016;Mesallati, Sheehy, Vinardell, Buckley, & Kelly, 2015;Vinardell, Sheehy, Buckley, & Kelly, 2012). In terms of instructive cues, a number of growth factors (GFs), hormones, and other small molecules are known to influence the development and regeneration of meniscal tissue.…”
mentioning
confidence: 99%